Circulating Th1, Th2, and Th17 Levels in Hypertensive Patients. (5th July 2017) - Ji, Qingwei; Cheng, Guojie; Ma, Ning; Huang, Ying; Lin, Yingzhong; Zhou, Qi; Que, Bin; Dong, Jianzeng; Zhou, Yujie; Nie, Shaoping
Abstract : Background . Evidence from experimental studies showed that Th1, Th2, and Th17 play a pivotal role in hypertension and target organ damage. However, whether changes in the circulating Th1, Th2, and Th17 levels are associated with nondipper hypertension and carotid atherosclerotic plaque in hypertension has yet to be investigated. Methods . Th1, Th2, and Th17 levels were detected using a flow cytometric analysis, and their related cytokines were measured by enzyme-linked immunosorbent assay in 45 hypertensive patients and 15 normotensive subjects. Results . The frequencies of Th1 and Th17 in hypertensive patients, especially in nondipper patients and patients with carotid atherosclerotic plaque, were markedly higher than those in the control group; this was accompanied by higher IFN- γ and IL-17 levels. In contrast, the Th2 frequencies and IL-4 levels in hypertensive patients, especially in nondipper patients and patients with carotid atherosclerotic plaque, were significantly lower than those in the control group. Conclusions . The changes in Th1, Th2, and Th17 activity are associated with the onset of the nondipper type and carotid atherosclerotic plaque in hypertensive patients.